Prandtl steady rotary current in an upright cylindrical container - Timokha, A.N. (Reports of the National Academy of Sciences of Ukraine, 2018)
The quantifying of the experimentally-known (Prandtl, 1949) steady rotary current during the swirl-type sloshing is first given. The current is treated as the sum of the mean wave (pseudo-) momentum through the meridional cross-section and the mean wave Eulerian flow, which is governed by the Craik—Leibovich equation. The constructed analytical inviscid theory is supported by existing experimental data.